Comparison of Perception and Implementation of Mathematical Physics for Matrices - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Simamora, Nadia Natalia (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2021)
Perception is a person's assessment of the object or information. The purpose of this study was to determine how students perceive and see which students have a positive perception of the e-module physics-mathematics matrix based on gender differences. The type of research used is survey research. The research approach used is quantitative research. The research population is Jambi University physics education students with a total sample of 120 students. The data analysis technique used is descriptive statistical data analysis and inferential data analysis with Anova and post hoc Tukey B tests. The results of the study through the Anova test showed that female students and male students obtained sig. smaller than 0.05, namely 0.001 and 0.037, which means that the perception is significantly different from the post hoc results of the Anova test as a whole, indicating that the average perception does not have a significant difference. Male students have a more positive perception than female students. Gender differences that exist in students have an influence on student perceptions. Student perceptions can be used as a guide for lecturers to choose learning media that will be used in the classroom. This research can be used as a guideline for the development of student perception assessments on the mathematical physics e-module in the future with an update in this study, namely student perceptions of the mathematics physics e-module based on gender differences.